Above and beyond Short-Term Mating, Long-Term Mating is Uniquely Tied to Human Personality - Nicholas S. Holtzman (Evolutionary Psychology, 2013)
To what extent are personality traits and sexual strategies linked? The literature does not provide a clear answer, as it is based on the Sociosexuality model, a one-dimensional model that fails to measure long-term mating (LTM). An improved two-dimensional model separately assesses long-term and short-term mating (STM; Jackson and Kirkpatrick, 2007 ). In this paper, we link this two-dimensional model to an array of personality traits (Big 5, Dark Triad, and Schizoid Personality). We collected data from different sources (targets and peers; Study 1), and from different nations (United States, Study 1; India, Study 2). We demonstrate for the first time that, above and beyond STM, LTM captures variation in personality.